Publisher Correction: GWAS of bone size yields twelve loci that also affect height, BMD, osteoarthritis or fractures - Unnur Styrkarsdottir (Nature Portfolio, 2019)
The original HTML version of this Article was updated shortly after publication to add links to the Peer Review file. In addition, affiliations 16 and 17 incorrectly read ‘School of Medicine Sydney, University of Notre Dame Australia, Sydney, WA, 6160, Australia’ and ‘St Vincent’s Clinical School, University of New South Wales Medicine, University of New South Wales, Sydney, NSW, 2052, Australia.’ This has now been corrected in both the PDF and HTML versions of the Article.